COMING OF FRIABLE MATERIAL TO THE SOUTH CASPIAN COASTAL ZONE AND DELIVERY OF IT ALONG THE COAST (Proceedings of the YSU C: Geological and Geographical Sciences, 2010)
Main factors, contributing to coming of friable material to the South Caspian coastal zone, are examined. It is marked, that alongshore currents, prevailing in this area winds of northern directions, are of great significance in delivery of this material along the coast.
Keywords: South Caspian zone; northern winds; clastic material